PENGARUH KEPERCAYAAN DIRI DAN KEMAMPUAN KOMUNIKASI TERHADAP KEMAMPUAN PUBLIC SPEAKING MAHASISWA PGSD - INDRASWATI, DYAH; HUSNIATI, HUSNIATI; ERMIANA, IDA; WIDODO, ARIF; MAULYDA, MOHAMMAD ARCHI (UIN Antasari Banjarmasin, 2020)
This study aims to determine: (1) The effect of self-confidence on the ability of public speaking; (2) The effect of communication skills on public speaking skills; (3) The effect of self confidence and communication ability on public speaking ability of Elementary School Teacher Education Students 2019, Faculty of Teacher Training and Education, University of Mataram. This research is an ex post facto study using a quantitative data approach. The subjects in this study were students of class 2019, amounting to 345 and then taken as many as 38% of the population of around 131 students. Analysis Methods of data collection using a questionnaire. Test the validity of the instrument using Product Moment correlation and reliability testing using Alpha Cronbach. Data analysis uses descriptive statistical analysis; analysis prerequisite test consisting of normality test, linearity test, and multicollinearity test; and regression analysis consisting of a simple linear regression test and multiple linear regression test. The results showed: (1) There was a positive and significant effect of self- confidence on the public speaking ability. (2) There is a positive and significant influence of communication ability on the public speaking ability. (3) There is a positive and significant influence of self-confidence and communication ability on the public speaking ability.